Analysis of the Annual Influenza Vaccination Event Hosted by the Riley County Health Department - Pearson, Jessica (My University, 2018)
This field experience was accomplished during an internship at the Riley County Health Department (RCHD) from October 2017 to April 2018. The internship was performed under the guidance of Andrew Adams, the Public Health Emergency Preparedness Coordinator for RCHD. The purpose of the field experience was to analyze the potential economic benefit and overall outreach success of an annual influenza vaccination event (named "Okt-FLU-ber Fest") provided by RCHD. It is important for RCHD employees to understand the impact these annual clinics have on the community. The main objective of this field experience was to help determine this information for the health department. A cost-benefit analysis was done by configuring the outgoing cost to both the health department to provide the event and to the public to attend and receive a vaccination. Additionally, the potential averted costs of influenza illness to the public were determined, and these values were compared to assess the potential economic benefit of receiving a flu vaccination at Okt-FLU-ber Fest. The results of the cost-benefit analysis suggested that the flu vaccine provides a substantial potential economic benefit to vaccinated individuals, as well as to Riley County. The results showed that the potential costs averted from not being ill with influenza or having more mild symptoms are greater than the expenses for the vaccination outreach effort. Additionally, Okt-FLU-ber Fest proved to be successful in terms of reaching the focal target age population of school-aged individuals. Outreach to areas of low median household income and high poverty status proved to be mostly successful. This information will be used to guide the Riley County Health Department in increasing their outreach efforts and ultimately improve the health of the community. The health department can now proceed with future planning for this annual event by targeting certain areas for education efforts, increasing advertisement of the event, and strategically placing mobile clinics.
Keywords: Okt-Flu-Ber-Fest; RCHD; cost-beenfit; public health